Finance, Trade and Economic Growth in Thirteen Asian Developing Countries - Tan, Slow Hooi (2000)
The main purpose of this study is to empirically assess the impact of financial deepening, export and investment, on economic growth in thirteen Asian developing economies. To achieve that end, the bivariate relationship between economic growth and three macroeconomic variables are tested through these bivariate models, namely: finance-led, export-led and investment-led. To address the mis-specification problem inherent in the bivariate studies, a multivariate V AR framework is then utilised to investigate the long-run relationships among these four variables. Annual data is used in the analysis covering the period from as early as 1950 to 1996. The Asian countries selected included Singapore, South Korea, Taiwan, Indonesia, Malaysia, Thailand, India, the Philippines, Bangladesh, Myanmar, Nepal, Pakistan and Sri Lanka. The empirical evidence obtained from this study suggest the following: for the bivariate studies, results from the finance-led model suggest a bi-directional relationship between financial deepening and economic growth in South Korea,Taiwan, Bangladesh and Pakistan. For Singapore, Malaysia, Thailand, India and Myanmar, the evidence supported the "demand following" hypothesis. For the exportled model, causality results on export-led growth versus growth-led export are mixed and, in some cases, contradictory. When investment-led model is utilised, there exhibit one-way Granger causal relationship from investment to growth for South Korea and Thailand whereas the reverse relationship is shown in Singapore, Indonesia, Malaysia and Sri Lanka. The feedback relationship is found in the case of Taiwan, Bangladesh and Pakistan. Under the multivariate V AR framework, long-run relationships between the investigated variables are identified in a cointegrating framework, suggesting the increasing degree of interdependence of these three macroeconomic variables with economic growth. Overall result has purported the significance of open economy structure, and outward looking trade policies in stimulating the economic growth of many developing economies. Hence, the continuation of open-door economic policies in developing economies is warranted, and integrating these economies more closely to the international economies.